Penerapan Green Banking di Lingkungan Bank BJB Syariah Indonesia - Siti Khodijah; Muhammad Iqbal Fasa; Suharto Suharto (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2023)
Issues related to the environment, maintaining ecological balance, and ecological sustainability have become topics of discussion worldwide. Organizations and consumers understand the importance of the environment for human survival, especially in the business community, which must integrate environmental protection into its business operations. The current banking industry must consider environmental aspects in its behavior and operations, namely green banking. This study aims to find out how green banking is implemented in the Bank BJB Syariah environment. The research method is a qualitative descriptive analysis using secondary data. The study results show that the BJB Syariah Bank has implemented several green banking programs, namely: the application of green principles with green financing use of water, paper, and waste treatment.